Ferroic behavior induced by oxygen vacancies in Mn-doped ZnO compounds. Issue 174 (1st September 2016) - Souza, N. E.; Portes, P. N.; Sato, F.; Silva, D. M.; Cótica, L. F.; Santos, I. A.; Pineda, E. A. G.; Hechenleitner, A. A. W.; de Melo, M. A. C.
Abstract: Mn-doped ZnO nanoparticles were successfully synthesized through the sol–gel technique. X-ray diffraction results showed that Mn doping did not disturb the hexagonal wurtzite structure of ZnO and no secondary phases were identified. Raman studies indicated the presence of defects in the form of oxygen vacancy clusters created due to Mn doping. Ferromagnetic-like curves were determined at room temperature for the sample with low doping (2% Mn). The results indicate that the observed ferromagnetism at room temperature can essentially be attributed to interactions mediated by magnetic impurities throughout the large number of oxygen vacancies created by Mn ions.